The effectiveness of Aloe vera barbadensis bioactives on laying hens on commercial farmers - Tiurma Pasaribu; A.P Sinurat; T Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2006)
A field trial was conducted to study the effectiveness of dry gel Aloe vera (DG) as a feed additive for laying hens in commercial farms. The trial was consisted of two treatments, one was control, commonly used farmer ration containing antibiotic of zinc bacitracin at 0.5 g/kg and the second feed containing DG equal to 1.0 g/kg. Every treatment had two replicates with 504 Loghman laying hens. The hen day production (% HD), egg weight, feed consumption, feed conversion ratio (FCR), egg quality comprising yolk colour, albumin and yolk weights, egg shell eight and thikness, and mortality were observed for 24 weeks. The results showed that feed consumption, % HD, egg weight, FCR, yolk colour, albumin weight, yolk weight, egg shell weight, and egg shell thickness were not significantly different (P>0.05) between the control and DG treatment, except for the Haugh unit (HU). Thus, it can be concluded that Aloe vera bioactives has the same effectiveness as antibiotic as a feed additive at the level of commercial farms. Key Words: Laying Hens, Egg Production, Egg Quality, Aloe vera barbadensis Bioactives, Antibiotic